Synthesis of polyrotaxanes consisting of multiple α-cyclodextrin rings threaded on reverse Pluronic PPO-PEO-PPO triblock copolymers based on block-selected inclusion complexation - Yang, C. (2014)
10.1016/j.eurpolymj.2009.01.020